Cuphea spp.: antichemotactic study for a potential anti-inflammatory drug. Issue 24 (17th December 2021) - Santos, Marí C.; Soares, Krissie D.; Beltrame, Betina M.; Bordignon, Sérgio A. L.; Apel, Miriam A.; Mendez, Andreas S. L.; Henriques, Amélia T.
Abstract: Cuphea genus (Lythraceae) popularly known in Brazil as " sete-sangrias ", it's described as antimicrobial, anti-inflammatory, diuretic and antihypertensive mainly. Investigating the chemotactic ability plays an important role in the identification of new anti-inflammatory agents. Thus, this research aims to assay the antichemotactic activity of hydroethanolic extracts of C. calophylla, C. carthagenensis, C. glutinosa, and C. racemosa as well as the compounds miquelianin and myricitrin. The antichemotactic activity of the hydroethanolic extracts, miquelianin, and myricitrin were assayed at concentrations 0.001 to 10  µg/mL in the lipopolysaccharide-induced chemotaxis on rat polymorphonuclear neutrophils. All the assayed samples displayed antichemotactic activity with reduction of the neutrophil migration in the range of 4.46-100%, and an IC50 value in the range of 0.30-1.24  µg/mL. Thus, this study demonstrates that the extracts hydroethanolic of Cuphea species, miquelianin, and myricitrin display a significant antichemotactic activity. Therefore, in future studies, extracts from Cuphea spp. could be used as anti-inflammatory drugs. Graphical Abstract: UF0001